Chromosomal location and relationships between the two ribosomal gene families in three lobsters (Crustacea, Decapoda) - SALVADORI, SUSANNA; COLUCCIA, ELISABETTA; DEIDDA, FEDERICA; LOBINA, CINZIA; DEIANA, ANNA MARIA (Chromosome Research, 2016)
The European lobster Homarus gammarus L., theAmer- ican lobster H. americanus H. Milne Edwards and the norway lobster Nephrops norvegicus L. are the most commercially important and studied species of Nephropidae.H.gammarus andN.norvegicus arewidely distributed in the estern side of the North Atlantic ocean and in the Mediterranean sea while H. americanus is commonly found in the western Atlantic. Nephrops and Homarus are considered closely related genera further- more, differences between the two Homarus species are very slight. Although their economic value, the cytoge- netics of lobsters remains poorly understood, due to tech- nical constraints in obtaining good chromosomal prepa- rations as well as the features of the chromosome com- plement. In fact thekaryotype of the three lobsters ismade upof a highnumber of little sizechromosomes,more than 100 in all species; furthermore, in N. norvegicus and H. americanus supernumerary chromosomes have been de- tected. Till now physical mapping studies in crustacean decapods are scarce. In this study we localized on the chromosomes of the three species the major (45S rDNA) and the minor (5S rDNA) ribosomal gene families by the use of doubleFISHwhich allowed to deepen the relation- ships between the two ribosomal families. 45SrDNA FISH localized the major ribosomal gene family in 6 chromosome pairs both in H. americanus and in H. gammarus, and in 8 pairs inN. norvegicus. In all the three specie 5S rDNA FISH localized the minor ribosomal gene family in a single chromosome pair, different from theNOR-carryingchromosomepairs in the twoHomarus species. In N. norvegicus both the ribosomal families are located in the samemedium-sized acrocentric pair.More- over we hybridized the pentameric telomeric repeat (TTAGG)n that appears to be the most widespread telo- mere repeat in Arthropods; the FISH produced bright fluorescent signals at the end of all chromosomes and, additionally, somelarge telomeric signals were present in the Homarus species. This study was supported by the ...